M15 Antifibrotic medications for idiopathic pulmonary fibrosis (IPF): a real world single centre experience of 447 patients over a 6 year period. (12th November 2019) - Harris, E; Harding, K; McLellan, T; Babu, A; Verghese, P; Parfrey, H; Simler, N; Fiddler, C; Thillai, M
Abstract : We report a retrospective analysis of 447 patients with IPF treated from 2013 to 2019 at the Royal Papworth Hospital UK. In terms of single centre data, we believe this is the largest collection reported to date. All patients started on medication are recorded on a database; this was accessed on 25/06/19. Statistical analysis was performed with Graphpad Prism. Mean age was 71 years with male predominance (87%). Over the 6 year period, more patients were started on pirfenidone (58%) vs. nintedanib (42%). However when analysed from late 2015 onwards (when both drugs were fully available) we found an increase in nintedanib (59%) vs. pirfenidone (41%). Time from diagnosis at MDT to initiation of medication steadily dropped from a mean of 196 days in 2016, 112 in 2017, 56 in 2018 and 28 in the first 6 months of 2019 (figure 1a, p<0.01). Drug persistence is improving; 56 patients persisted >6 weeks in 2015 (85% of patients started that year), 75 (95%) in 2016, 79 (96%) in 2017 and 111 (97%) in 2018. These findings mirrored persistence >6/12 months. Nurse led telephone clinics began in 2017 to review medications at 6 weeks post drug initiation. These may have increased persistence; 46 of 78 patients (59%) persisted >6 months in the 12 months prior to starting clinics vs. 72 of 91 (79%) in the following 12 months. 113 (25%) of all patients switched between antifibrotics and this is becoming more common over time. Reviewing all new patients prescribed medication from 01/01/16–01/01/19, 73 out of 176 (41%) patients stopped nintedanib and 83 of 148 patients (56%) stopped pirfenidone. Fewer patients experienced a dose reduction on nintedanib (42%, predominantly due to lower GI side-effects) compared to pirfenidone (63%, predominantly nausea and fatigue). Median duration on nintedanib was significantly greater (304 days) vs. pirfenidone (214 days) figure1b, p=0.002. Accepting inherent limitations of retrospective data, we show differences in drug prescribing, decrease in time to initiating treatment and increase in persistence over time. This may reflect an increased learning curve for managing side-effects as well as novel management strategies e.g. virtual MDT, shared care and nurse led clinics.